2020
DOI: 10.1259/bjr.20200548
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of an empty bladder filling protocol for localised prostate volumetric modulated arctherapy (VMAT): early results of a single institution service evaluation

Abstract: Objective: To examine the impact of an empty bladder filling protocol on patients receiving radical RT for localised prostate cancer on post RT toxicity and biochemical progression free survival (bPFS). Methods and materials: Records of patients receiving radical external beam RT (EBRT) for localised prostate cancer with a full or empty bladder were reviewed. These included the bladder size on planning CT, daily online image guided RT (IGRT) setup data, treatment time and post treatment follow up data.These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…They found non-inferiority of an empty bladder filling protocol comparing to a full bladder filling protocol in respect to biological progression-free survival and GU and GI toxicities. 42 Our clinical findings in image-guided SSPT were consistent with the reports of X-ray therapy from Byun et al and Chetiyawardana et al and, therefore, a bladder-emptying protocol could be preferable by virtue of reducing BV variation. Past studies which found correlations between BV and clinical outcome is for early GU toxicity and needs to be evaluated further for late toxicities but the inclusion of patients who received irradiation or surgery of the pelvis in their series may be related to the correlation between BV and GU toxicity.…”
Section: Discussionsupporting
confidence: 90%
“…They found non-inferiority of an empty bladder filling protocol comparing to a full bladder filling protocol in respect to biological progression-free survival and GU and GI toxicities. 42 Our clinical findings in image-guided SSPT were consistent with the reports of X-ray therapy from Byun et al and Chetiyawardana et al and, therefore, a bladder-emptying protocol could be preferable by virtue of reducing BV variation. Past studies which found correlations between BV and clinical outcome is for early GU toxicity and needs to be evaluated further for late toxicities but the inclusion of patients who received irradiation or surgery of the pelvis in their series may be related to the correlation between BV and GU toxicity.…”
Section: Discussionsupporting
confidence: 90%
“… 36 Although unable to measure bladder volume because of the restricted field of view on the CBCT, it was identified that differences in bladder volume between CT planning and treatment were present. Treating with an empty bladder may provide a more reproducible and reliable method of ensuring consistency between treatments and reduced intra-fraction motion 37 but potentially at the expense of increased total bladder dose.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent bladder filling regardless of the protocol used, led multiple groups to investigate treating prostate cancer with radiation therapy on empty bladder. The rationale is that it is easier to obtain consistently empty bladder than a full one, while trying to reduce bowel dose by rigorous treatment planning [14,24,25]. Consistent empty bladder throughout the treatment needs continuous drainage with a Foley catheter especially when using ultrahypofrationaed doses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the challenges of obtaining consistently full bladder, some groups proposed utilizing consistently empty bladder when treating the prostate gland and seminal vesicles only with RT [14,24,25]. Chetiyawardana et al reported that empty bladder filling protocol of EBRT for localized prostate cancer resulted in noninferior treatment outcomes compared to patients treated with full bladder [24]. Greco et al utilized a Foley catheter to empty the bladder during 24 Gy single fraction RT to the prostate, and reported that the treatment can be safely delivered, with low acute toxicity [14].…”
Section: Empty Bladder As a Strategy For Reproducing Consistent Bladder Fillingmentioning
confidence: 99%